2013
DOI: 10.1016/j.jcv.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies to human papillomavirus (HPV) pseudovirions correlate with natural infection for 13 genital HPV types

Abstract: Serum antibodies to human papillomavirus (HPV) pseudovirions correlate with natural infection for 13 genital HPV types.Faust, Helena; Jelen, Mateja M; Poljak, Mario; Klavs, Irena; Učakar, Veronika; Dillner, Joakim General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Our study population was not HPV-na€ ve, and as a result a proportion of "incident" infections might actually have been reactivations of long-standing infections, diluting our results. Finally, there is no standardized serologic assay for detection of HPV antibodies (9,31). In a previous article, we compared 3 serologic assays, including the MIA used in the current study, and observed good correlations for both naturally induced and vaccine-derived HPV-specific antibody levels (32).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our study population was not HPV-na€ ve, and as a result a proportion of "incident" infections might actually have been reactivations of long-standing infections, diluting our results. Finally, there is no standardized serologic assay for detection of HPV antibodies (9,31). In a previous article, we compared 3 serologic assays, including the MIA used in the current study, and observed good correlations for both naturally induced and vaccine-derived HPV-specific antibody levels (32).…”
Section: Discussionmentioning
confidence: 53%
“…Analyses were limited to the 7 high-risk HPV types that could be detected by both the serology and DNA genotyping methods used, i.e., types 16,18,31,33,45,52, and 58. Samples positive for one or more of these 7 HPV types were designated hrHPVpositive in this article; samples negative for all of these 7 high-risk types were categorized as hrHPV-negative.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Equations and detailed parameter tables are provided (SI Appendix, Table S1). We parameterized the type-specific HPV clearance rate in women and the type-specific antibody protection against reinfection from the control arm of the PATRICIA clinical trial (26,39), the type-specific clearance rate in men from the HIM cohort study (40), the type-specific probability of developing antibodies from the Slovenian HPV prevalence survey (41), and the type-specific rate of antibody decay from the Finnish Family HPV study (42).…”
Section: Methodsmentioning
confidence: 99%
“…Infection with certain genotypes of HPV has been linked with cervical cancer development. In china vaccines were developed to combat HPV infection, consequently, the most prevalence HPV types should be determined in each region (Arbyn et al, 2010;Faust et al, 2013). The Uyghur women who live in desert regions have the unique lifestyles and religion has the highest prevalence of cervical cancer in China.…”
Section: Introductionmentioning
confidence: 99%